Pengaruh Disiplin Kerja Terhadap Produktivitas Kerja Dosen di Universitas Muhammadiyah Palopo - Hardianti, Iin; Sampetan, Suparni; Sari, Nispa (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to determine the effect of work discipline on the work productivity of lecturers at Muhammadiyah University of Palopo. This research uses a quantitative approach. Sampling in this research uses the census method by using the entire population as a sample, namely 150 lecturers at Muhammadiyah Palopo University. The results showed that work discipline has a significant positive effect on lecturer productivity at Muhammadiyah University of Palopo.